Effects of isoflurane on echocardiographic parameters in healthy dogs - Sousa, Marlos G. [UNESP]; Carareto, Roberta [UNESP]; De-Nardi, Andrigo B. [UNESP]; Brito, Fabio L. C. [UNESP]; Nunes, Newton; Camacho, Aparecido Antonio [UNESP] (Blackwell Publishing, 2008)
Obejective To study the echocardiographic effects of isoflurane at an end-tidal concentration approximating 1.0 times the minimum alveolar concentration (MAC) in healthy unpremedicated dogs.Study design Prospective experimental trial.Animals Sixteen mature mongrel dogs of either sex weighing 11.06 +/- 2.72 kg.Methods After performing a baseline echocardiogram in the awake animal, anesthesia was induced with increasing inspired concentrations of isoflurane via a face mask until tracheal intubation was possible. Following intubation, the end-tidal concentration was decreased to 1.4% for the rest of the anesthetic period. Serial echocardiograms were recorded at 25, 40, and 55 minutes after the end-tidal concentration was reached.Results No changes were observed in heart rate. However, significant decreases were seen in left ventricular end-diastolic diameter (Mean maximal change: 13.8%), interventricular septal thickness during systole (15.2%), interventricular septal thickening fraction (72.2%), left ventricular free wall thickening fraction (63.5%), ejection fraction (39.9%), and fractional shortening (46.7%). In addition, peak flow velocities across mitral, pulmonic, and aortic valves were significantly lower than baseline values. Decreases were also observed in end-diastolic left ventricular volume index (approximately 32.1% from the awake value), stroke index (58.2%), and cardiac index (55.3%) when compared with awake measurements.Conclusions Our results indicate that 1 x MAC isoflurane caused significant myocardial depression in healthy dogs. These changes in myocardial function need to be considered carefully when isoflurane is to be used in dogs with poor cardiovascular reserve.
Keywords: echocardiography; Hemodynamics; left ventricular function; volatile anesthetics